Analysis of genetic variability and trait association in rice (Oryza sativa L.) - Thirumalraj, S; Bonipas , AJ; Gnanamalar , RP; Swaminathan, Manonmani; Gopalakrishnan , C; Raveendran , M; Ramalingam, J (Plant Science Today, 2025)
Rice is a staple food for billions of people worldwide. In recent years unpredictable weather patterns, making rice cultivation more challenging and threatens its productivity. To ensure food security, developing high-yielding and climate-resilient rice varieties is essential. This requires a deep understanding of genetic variability and the relationships between key agronomic traits. Thus, the present study explores the genetic variability, as well as the major yield attributes of a segregating population derived from black rice genotypes, to formulate an effective selection strategy. In this research, 188 F2 plants derived from crosses between the improved Chakhao Amubi and improved Co 51 varieties were analysed and superior progenies were forwarded to F3 generation. The variability study in the F₂ population revealed substantial variation for single plant yield and related yield attributes such as productive tillers and panicle length. High heritability estimates across all traits, along with a significant genetic advance over the mean for yield and major yield components, indicate that phenotypic selection would be effective. Principal Component Analysis (PCA) further confirmed the extensive variability present in the F₂ population. Correlation and path analysis highlighted panicle length and flag leaf length as key contributors to single plant yield, emphasizing their importance in selection strategies. The combined analysis of the F₂ and selected F₃ families revealed that single plant yield is predominantly governed by additive gene action, as evidenced by significant inter-generational correlation and high narrow-sense heritability. Furthermore, the observed positive selection response for yield suggests that simple phenotypic selection can lead to substantial genetic gain in rice